Childhood adversity and self-poisoning: A hospital case control study in Sri Lanka - Rajapakse, Thilini; Russell, Abigail Emma; Kidger, Judi; Bandara, Piumee; López-López, José A.; Senarathna, Lalith; Metcalfe, Chris; Gunnell, David; Knipe, Duleeka (PloS one, 2020)
Adverse childhood experiences (ACE) have been recognized as an important risk factor for suicidal behaviour among adults, but evidence from low and middle-income countries is lacking. This study explored associations between ACE and hospital admission due to non-fatal self-poisoning in Sri Lanka. This was a case-control study. Adults admitted to a tertiary care hospital for medical management of self-poisoning were included as cases, and age and sex matched controls were recruited from the outpatient department. ACE were measured using the World Health Organization's Childhood Adversity Scale. Logistic regression models adjusting for age, sex, ethnicity, and religion were used to quantify the association between ACE and self-poisoning. The study included 235 cases and 451 controls. Cases were 2.5 times (95% CI 1.8, 3.6) more likely to report an ACE than controls and had higher ACE scores. Childhood physical abuse (OR 4.7, 95% CI 1.2, 19.0) and emotional abuse or neglect (OR 3.7, 95% CI 1.3, 10.1, and 3.7, 95% CI 2.3, 6.0 respectively), increased the risk of self-poisoning in adulthood, as did witnessing household violence (OR 2.2, 95% CI 1.4, 3.4), growing up in a household with a mentally ill or suicidal household member (OR 2.1, 95% CI 1.2, 3.4), and experiencing parental death/separation/divorce (OR 3.1, 95% CI 2.0, 4.9) as a child. Reducing exposures to ACEs should be a priority for prevention of suicide and self-harm in Sri Lanka. Innovative methods to increase support for children facing adversity should be explored.